Implicatures in the Film Home Sweet Loan by Director Sabrina Rochelle: Types and Functions - Rades Kasi; Hermandra; Tria Putri Mustika (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the types and functions of implicature in the film Home Sweet Loan directed by Sabrina Rochelle. This film was selected as the object of the study because the dialogues among the characters contain many implied meanings that reflect social realities, economic pressures, and psychological conflicts experienced by young people. Implicatures in this film emerge through indirect communication related to the social, emotional, and relational contexts among characters, making it interesting to analyze using pragmatic studies. This research employs a descriptive qualitative approach. The data consist of utterances or dialogues among the characters in the film Home Sweet Loan that contain implicatures. The data were collected through observation and note-taking techniques by watching the film repeatedly and then transcribing relevant conversations. Furthermore, the data were analyzed by classifying the types and functions of implicature based on Grice’s implicature theory. The results of the study indicate that there are two types of implicature in the film Home Sweet Loan, namely conventional implicature and non-conventional implicature. Conventional implicatures are found in utterances whose implied meanings can be generally understood, while non-conventional implicatures appear in utterances that require an understanding of the social and emotional contexts of the characters. In addition, the functions of implicature identified include assertive, directive, expressive, commissive, and declarative functions. Thus, the use of implicature in the film Home Sweet Loan enriches communication, portrays the social realities of young people, and effectively conveys social messages. This study is expected to contribute to pragmatic studies, particularly implicature analysis in film media, and serve as a reference for students, researchers, and film practitioners in understanding the use of implicature as a communication strategy in film dialogue.